Efficient second harmonic generation at quasi-bound states in the continuum in hybrid nanostructures of 2D plasmonic array and waveguide - Liu, Di; Huo, Yanyan; Ren, Yingying; Cai, Yangjian; Ning, Tingyin (Results in physics, 2023)
We numerically investigate the second harmonic generation (SHG) in hybrid plasmonic–photonic structures consisting of an array of periodic gold nanodisks covered by a nonlinear dielectric layer. In the designed hybrid systems, symmetry-protected bound states in the continuum (BICs) at normal incidence, and Friedrich–Wintgen BICs due to the coupling between localized surface plasmon resonances (LSPRs) and waveguide modes at oblique incidence, are observed under both transverse-electric (TE) and transverse-magnetic (TM) polarized illuminations. SHG near the BICs is studied, and the dramatically enhanced nonlinear optical response at quasi-BICs is obtained. Such enhancement is ascribed to the enhanced local field due to hybrid modes of LSPRs and photonic modes. The results indicate that hybrid plasmonic-dielectric systems supporting BICs at both TE- and TM-polarized incidences are promising platforms for linear and nonlinear photonic devices. [Display omitted] •Two types of BICs in the hybrid nanostructure at both TE- and TM-polarization are observed.•Evolution of second harmonic generation near BICs is demonstrated.•Efficient SHG at quasi-BICs at both TE- and TM-polarized fundamental lights is obtained.